How does international investment affect national innovation? - Cong, Shufeng; Lee, Chin; Mirzaliev, Sanjar; Allayarov, Piratdin; Zheng, Huiyu (John Wiley and Sons, 2026)
This paper examines the impact of international investment on national innovation, focusing on the role of inward foreign direct investment (IFDI), outward foreign direct investment (OFDI), and two-way foreign direct investment (DFDI). Analysis of cross-country panel data from 2011 to 2023 using the double machine learning method reveals that IFDI significantly promotes national innovation through technology transfer and competitive pressure. In contrast, OFDI and DFDI demonstrate a more limited direct impact on innovation. The results of propensity score matching–difference-in-differences show that ASEAN's Regional Comprehensive Economic Partnership policies boost national innovation. Additionally, mechanism tests show that economic freedom moderates the relationship between international investment and national innovation. Greater economic freedom alleviates market access barriers and promotes the integration of foreign investment into the local innovation ecosystem, thereby amplifying the positive impact of IFDI. The analysis also points out that the relationship between international investment and innovation varies across regions and levels of development, with the impact of IFDI being stronger in developing countries and Asian countries. The study therefore emphasises the importance of tailoring international investment strategies to specific economic and regional circumstances to maximise their contribution to national innovation. Policymakers should focus on improving the quality of inward investments, supporting outward investment for technology acquisition, and promoting a balanced two-way investment system to ensure innovation-driven growth.